Sedation or general anesthesia for transcatheter aortic valve implantation (TAVI) - Mayr, N. Patrick (J Thorac Dis, 2015)
Transfemoral transcatheter aortic valve implantation (TAVI) is nowadays a routine therapy for elderly patients with severe aortic stenosis (AS) and high perioperative risk. With growing experience, further development of the devices, and the expansion to “intermediate-risk” patients, there is increasing interest in performing this procedure under conscious sedation (TAVI-S) rather than the previously favoured approach of general anesthesia (TAVI-GA). The proposed benefits of TAVI-S include; reduced procedure time, shorter intensive care unit (ICU) length of stay, reduced need for intraprocedural vasopressor support, and the potential to perform the procedure without the direct presence of an anesthetist for cost-saving reasons. To date, no randomized trial data exists. We reviewed 13 non-randomized studies/registries reporting data from 6,718 patients undergoing TAVI (3,227 performed under sedation). Patient selection, study methods, and endpoints have differed considerably between published studies. Reported rates of in-hospital and longer-term mortality are similar for both groups. Up to 17% of patients undergoing TAVI-S require conversion to general anesthesia during the procedure, primarily due to vascular complications, and urgent intubation is frequently associated with hemodynamic instability. Procedure related factors, including hypotension, may compound preexisting age-specific renal impairment and enhance the risk of acute kidney injury. Hypotonia of the hypopharyngeal muscles in elderly patients, intraprocedural hypercarbia, and certain anesthetic drugs, may increase the aspiration risk in sedated patients. General anesthesia and conscious sedation have both been used successfully to treat patients with severe AS undergoing TAVI with similar reported short and long-term mortality outcomes. The authors believe that the significant incidence of complications and unplanned conversion to general anesthesia during TAVI-S mandates the start-to-finish presence of an experienced cardiac anesthetist in order to optimize patient outcomes. Good quality randomized data is needed to determine the optimal anesthetic regimen for patients undergoing TAVI.